Cadmium(II) three‐dimensional coordination polymers constructed from 1, 3, 5‐tris(4‐carboxyphenoxy)benzene: synthesis, crystal structure, fluorescence and I2 sorption characterization. Issue 5 (17th April 2019) - Bai, Yuting; Han, Meirong; Wu, Enxi; Feng, Sisi; Zhu, Miaoli
Abstract : Two three‐dimensional Cd II coordination polymers (CPs) were obtained by the hydrothermal method under similar conditions except for the presence of an auxiliary 1, 4‐bis(imidazol‐1‐yl)benzene ligand in one of them. It was found that molecular I2 can move in and out of this latter CP freely without changes to the skeleton. Abstract : Two three‐dimensional (3D) Cd II coordination polymers, namely poly[[di‐μ‐aqua‐diaquabisμ5 ‐4, 4′, 4′′‐[benzene‐1, 3, 5‐triyltris(oxy)]tribenzoatotricadmium(II)] dihydrate], [Cd3 (C27 H15 O9 )2 (H2 O)4 ]·2H2 O n, (I), and poly[[aquaμ6 ‐4, 4′, 4′′‐[benzene‐1, 3, 5‐triyltris(oxy)]tribenzoato(μ‐formato)[μ‐1, 1′‐(1, 4‐phenylene)bis(1 H ‐imidazole)]dicadmium(II)] dihydrate], [Cd2 (C27 H15 O9 )(C12 H10 N4 )(HCOO)(H2 O)]·2H2 O n, (II), have been hydrothermally synthesized from the reaction system containing Cd(NO3 )2 ·4H2 O and the flexible tripodal ligand 1, 3, 5‐tris(4‐carboxyphenoxy)benzene (H3 tcpb) via tuning of the auxiliary ligand. Both complexes have been characterized by single‐crystal X‐ray diffraction analysis, elemental analysis, IR spectra, powder X‐ray diffraction and thermogravimetric analysis. Complex (I) is a 3D framework constructed from trinuclear structural units and tcpb 3− ligands in a μ5 ‐coordination mode. The central Cd II atom of the trinuclear unit is located on a crystallographic inversion centre and adopts an octahedral geometry. The metal atoms are bridged by four syn – syn carboxylate groups and two μ2 ‐water molecules to form trinuclear [Cd3 (COO)4 (μ2 ‐H2 O)2 ] secondary building units (SBUs). These SBUs are incorporated into clusters by bridging carboxylate groups to produce pillars along the c axis. The one‐dimensional inorganic pillars are connected by tcpb 3− linkers in a μ5 ‐coordination mode, thus forming a 3D network; its topology corresponds to the point symbol (4 2 .6 2 .8 2 )(4 4 .6 2 )2 (4 5 .6 6 .8 4 )2 . In contrast to (I), complex (II) is characterized by a 3D framework based on dinuclear cadmium SBUs, i.e. [Cd2 (COO)3 ]. The two symmetry‐independent Cd II ions display different coordinated geometries, namely octahedral [CdN2 O4 ] and monocapped octahedral [CdO7 ]. The dinuclear SBUs are incorporated into clusters by bridging formate groups to produce pillars along the c axis. These pillars are further bridged either by tcpb 3− ligands into sheets or by 1, 4‐bis(imidazol‐1‐yl)benzene ligands into undulating layers, and finally these two‐dimensional surfaces interweave, forming a 3D structure with the point symbol (4.6 2 )(4 7 .6 14 ). Compound (II) exhibits reversible I2 uptake of 56.8 mg g −1 with apparent changes in the visible colour and the UV–Vis and fluorescence spectra, and therefore may be regarded as a potential reagent for the capture and release of I2 .